The Role of Trade Tariff Policy on US Supply Chain Imbalance and Trade Deficits Reduction: Evidence from Trend and Univariate Analyses - Zaye, Ejiro (International Journal of Supply Chain and Logistics, 2025)
Purpose: Despite the free and lower trade tariff policy, the United States (US) has recorded a persistent trade deficit and trade imbalances in the last four decades ago, therefore, this study empirically investigates the role of trade tariff policy on US supply chain imbalance and trade deficits reduction. Methodology: The study employs simple random and stratified sampling techniques to analyses the trend and univariate. Secondary data from US Census Bureau of Economic Analysis Department of Commerce on US international trade in goods and services from 1852 to 2024 were analysed to drawn inferences. Findings: This study finds that US trade tariff policy is not automatic to reduce supply chain imbalances and trade deficits in the United States. The US trade liberalization policy is associated with supply chain imbalance and trade deficits while the U.S. trade protectionism policy accounted for more trade surplus and supply chain balance. Also the study finds that a minimum threshold of 10 percent US weighted trade tariff rate to reduce the US trade supply chain imbalance and trade deficits Unique Contribution to Theory, Practice and Policy: This study supports the protectionism trade theory over the trade liberalization theory to aggressively promote exports but reduces imports through a number of trade barriers like tariff rate, imports restriction, and currency depreciation (devaluation) to make trading partners imports dependence while protecting country’s domestic industry from foreign competition. Recommendations to the current US President, Trump is to set a minimum of 10 percent weighted tariff rates on all goods and services to other trading partners while US should imposes a higher weighted tariff rates above 10 to all goods and services from China to swiftly reduce US trade deficits and supply chain imbalance to be more effective than Trump former US President administration and also President Biden administration.